Association and Genetic Identification of Loci for Four Fruit Traits in Tomato Using InDel Markers - Liu, Xiaoxi; Geng, Xiaolin; Zhang, Hongchi; Shen, Huolin; Yang, Wencai (Frontiers in Plant Science, 2017)
Tomato (Solanum lycopersicum) fruit weight (FW), soluble solid content (SSC), fruit shape and fruit color are crucial for yield, quality and consumer acceptability. In this study, a 192 accessions tomato association panel comprising a mixture of wild species, cherry tomato, landraces, and modern varieties collected worldwide was genotyped with 547 InDel markers evenly distributed on 12 chromosomes and scored for FW, SSC, fruit shape index, and color parameters over two years with three replications each year. The association panel was sorted into two subpopulations. Linkage disequilibrium ranged from 3.0 Mb to 47.2 Mb across 12 chromosomes. A set of 102 markers significantly (p<1.19-1.30 x10-4) associated with SSC, FW, fruit shape, and fruit color was identified on 11 of the 12 chromosomes using a mixed linear model. The associations were compared with the known gene/QTLs for the same traits. Genetic analysis using F2 populations detected 14 and 4 markers significantly (p<0.05) associated with SSC and FW, respectively. Some loci were commonly detected by both association and linkage analysis. Particularly, one novel locus for FW on chromosome 4 detected by association analysis was also identified in F2 populations. The results demonstrated that association mapping using limited number of InDel markers and a relatively small population could not only complement and enhance previous QTL information, but also identify novel loci for marker-assisted selection of fruit traits in tomato.